Potential Applications of Somatic Experiencing® in Applied Sport Psychology. Issue 2 (3rd April 2023) - Samuel, Roy David; Brom, Danny
Abstract: In recent years, applied sport psychologists have become more open to "third wave therapies" that focus on the holistic promotion of human well-being. In this article, the potential application of body psychotherapy, Somatic Experiencing ® (SE™), is presented within the sport context. SE ™ focuses on resolving the symptoms of chronic stress and post-traumatic stress, among other things by directing the client's attention to internal sensations, both visceral (interoception) and musculoskeletal (proprioception and kinesthesis) to resolve a dysfunctional state of the autonomic nervous system. The basic tenets of the SE ™ framework are initially described with a short account of its effectiveness. Then, SE ™ intervention context and ethical considerations are discussed, followed by a hypothetical example of its application with a judoka who experienced stress following an unexpected loss in a competition. Reflections and recommendations for practitioners are provided.